Identification and expression analysis of P-type ATPase IIIA subfamily in Puccinia Striiformis f. sp. tritici - Yingjie Sun; Hong Tao; Hong Han; Yiping Zou; Yingyu Xue; Shiwen Chen; Fei Tao (BMC Genomics)
Abstract Background Puccinia striiformis f. sp. tritici (Pst) causes wheat stripe (yellow) rust disease, which is one of the most destructive diseases affecting wheat worldwide. ATPases, a class of membrane proteins, play an important role in material exchange and signal transduction both within and outside biological cells by transporting ions and phospholipids. In plant pathogens, P-type ATPases primarily participate in pathogen development and virulence regulation. However, the P-type ATPase of subfamily IIIA (PMA) has not yet been identified in Pst. To investigate the potential functions of the PMA gene family in Pst, we conducted a genome-wide bioinformatics analysis and examined the expression profiles of the PMA gene family. Results Six PMA genes were identified in the genome of P. striiformis f. sp. tritici (CYR34 race). The PMA proteins encoded by these genes ranged in length from 811 to 960 amino acids (aa). Each of the six PMA genes contained a typical ATPase IIIA H superfamily domain and was distributed across four chromosomes. Thirty-six major cis-regulatory elements were detected within the PMA gene family members. Elements such as the CGTCA-motif and TGACG-motif play significant roles in responding to environmental stresses and hormone signals. Quantitative PCR analysis revealed that the expression of the PMA04 gene was generally higher at 9 °C under various temperature stresses. The PMA06 gene typically exhibited higher expression levels at 16 °C. During the infection of Pst, the expression levels of PMA04, PMA05, and PMA06 were elevated at 72 h post treatment. Conclusions Our results indicate that the PMA gene family in the CYR34 strain comprises six PMA genes, which are crucial for managing temperature stress and pathogen infection, and exhibit a distinctive splicing pattern. This study not only identifies a target and direction for the development of new, efficient, and environmentally friendly control agents for wheat stripe rust but also establishes a foundation for analyzing its pathogenic mechanisms.